Microplastics in Seawater: Recommendations from the Marine Strategy Framework Directive Implementation Process - Gago, Jesus; Galgani, Francois; Maes, Thomas; Thompson, Richard C. (Frontiers in Marine Science, 2016)
Microplastic litter is a pervasive pollutant present in marine systems across the globe. The legacy of microplastics pollution in the marine environment today may remain for years to come due to the persistence of these materials. Microplastics are emerging contaminants of potential concern and as yet there are few recognised approaches for monitoring. In 2008, the EU Marine Strategy Framework Directive (MSFD, 2008/56/EC) included microplastics as an aspect to be measured. Here we outline the approach as discussed by the European Union expert group on marine litter, the technical Subgroup on Marine litter (TSG-ML), with a focus on the implementation of monitoring microplastics in seawater in European seas. It is concluded that harmonization and coherence is needed to achieve reliable monitoring.